A comparative study between cobblator and microdebrider assisted inferior turbinate reduction surgery - Jadhav, Santosh Govindrao; Mane, Balaji Shankarrao; Naikwadi, Kiran Bibhishan; Gavali, Rushali Madhukar (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Background: Inferior turbinate hypertrophy (ITH) management includes medical and surgical line which reduces the size of the turbinate. The surgical line of management includes old partial and total turbinectomy to newer technique as submucous inferior turbinate reduction (ITR) using cobblation, microdebrider, radiofrequency ablation, diathermy, cryotherapy, and laser therapy. Methods: Our study was duration based prospective observational study conducted between August 2021 to August 2022 in department of otorhinolaryngology at our institute with total of 160 patients who have undergone turbinate reduction surgery during 1 year duration. Half number of patients have undergone microdebrider assisted submucous inferior turbinate reduction surgery (group A) and remaining half number have undergone cobblator assisted submucous Inferior turbinate reduction surgery (group B). Comparison of pre-operative and postoperative data of each surgical technique was the aim of our study. Results: On comparing the nasal obstruction symptom evaluation (NOSE) score using unpaired t test, between the two techniques on each follow up days respectively, it was found that cobblation provided better improvement than microdebrider on each day and the results were highly significant with p value <0.01. On comparing the pre-operative and post-operative (day 60) inferior turbinate size using paired t test, the result of the test was statistically significant with p value <0.01 in both nostrils using both the techniques. Conclusions: Submucosal inferior turbinate reduction surgery for ITH using either microdebrider or cobblator technique shown better improvement in terms of NOSE score improvement, Inferior turbinate size reduction, mucocilliary transit time improvement.